EXPLORING THE THERAPEUTIC POTENTIAL OF CAPSICUM ANNUUM EXTRACT AGAINST BREAST CANCER IN SPRAGUE DAWLEY RATS - Zain ul Abedin; Imran Pasha; Masood Sadiq Butt; Muhammad Naeem Faisal (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Ethnopharmacological relevancy: Many studies showed that various segments of Capsicum annuum L, has therapeutic and ameliorative potential against cancer which is one of the major contributor for causing oxidative stress, adduct formation in genetic material and cell proliferation, etc. Aim of study: Current research was carried out to analyze anti-cancerous potential of Capsicum annuum extract in breast cancerous rats. Material and methods: Capsicum annuum ethanolic extract was attained via employing Soxhlet apparatus. This obtained extract was further utilized for research trial on rats. For this purpose, 50 healthy female rats were chosen for study, the rats were segregated into five groups, 10 rats in each group; G0 (negative control group), G1 (positive control group), G2 (doxorubicin as a standard drug), G3 and G4 (rats receiving capsicum extracts). Breast cancer in rats was induced by administering the single dose of DMBA (50mg/kg) through gavage. Blood samples were investigated for breast cancer biomarkers and serum biomarkers to analyze the outcome of treatments. Furthermore, tumor weight, volume, burden and incidence was also noticed along with histopathological examination of tissues. Results: The Capsicum annuum extracts prevented the rise in concentration of biomarkers of breast cancer in rats that are CA 15.3, CA 27.29 and CEA. Furthermore, the capsicum extracts also significantly improved the level of serum biomarkers such as TAC (Total antioxidant capacity) and TOS (Total oxidative stress) in breast cancerous rats. The tumor weight, volume, burden and incidence was significantly decreased in G2, G3 and G4 groups treated with doxorubicin and Capsicum annuum extracts. Histopathological examination of breast tissues showed that tissue damage was reversed in groups G3 and G4 treated with capsicum extracts.